Methanol extract of Inonotus obliquus improves type 2 diabetes mellitus through modifying intestinal flora - Ye, Xuewei; Wu, Kefei; Xu, Langyu; Cen, Yingxin; Ni, Jiahui; Chen, Junyao; Zheng, Wenxin; Liu, Wei (Frontiers in Endocrinology, 2023)
Type 2 diabetes mellitus (T2DM) poses a significant risk to human health. Previous research demonstrated that Inonotus obliquus possesses good hypolipidemic, anti-inflammatory, and anti-tumor properties. In this research, we aim to investigate the potential treatment outcomes of Inonotus obliquus for T2DM and discuss its favourable influences on the intestinal flora. The chemical composition of Inonotus obliquus methanol extracts (IO) was analyzed by ultra-high-performance liquid chromatography-Q extractive-mass spectrometry. IO significantly improved the blood glucose level, blood lipid level, and inflammatory factor level in T2DM mice, and effectively alleviated the morphological changes of colon, liver and renal. Acetic acid, propionic acid, and butyric acid levels in the feces of the IO group were restored. 16S rDNA gene sequencing revealed that the intestinal flora composition of mice in the IO group was significantly modulated. Inonotus obliquus showed significant hypoglycemic and hypolipidemic effects with evident anti-inflammatory activity and improved the morphological structure of various organs and cells. Inonotus obliquus increased the levels of short-chain fatty acids in the environment by increasing the population of certain bacteria that produce acid, such as Alistipes and Akkermansia, which are beneficial to improve intestinal flora disorders and maintain intestinal flora homeostasis. Meanwhile, Inonotus obliquus further alleviated T2DM symptoms in db/db mice by down-regulating the high number of microorganisms that are dangerous, such as Proteobacteria and Rikenellaceae_RC9_gut_group and up-regulating the abundance of beneficial bacteria such as Odoribacter and Rikenella. Therefore, this study provides a new perspective for the treatment of T2DM by demonstrating that drug and food homologous active substances could relieve inflammation via regulating intestinal flora.